2018
DOI: 10.18632/aging.101446
|View full text |Cite
|
Sign up to set email alerts
|

Common and unique transcriptional responses to dietary restriction and loss of insulin receptor substrate 1 (IRS1) in mice

Abstract: Dietary restriction (DR) is the most widely studied non-genetic intervention capable of extending lifespan across multiple taxa. Modulation of genes, primarily within the insulin/insulin-like growth factor signalling (IIS) and the mechanistic target of rapamycin (mTOR) signalling pathways also act to extend lifespan in model organisms. For example, mice lacking insulin receptor substrate-1 (IRS1) are long-lived and protected against several age-associated pathologies. However, it remains unclear how these part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 85 publications
(103 reference statements)
1
12
0
Order By: Relevance
“…Studies examining the transcriptomic and proteomic changes that occur during aging, or in response to interventions that ameliorate its effects, have revealed several conserved prolongevity processes, including many metabolic changes (Afschar et al, ; Dobson et al, ; Hahn et al, ; Murphy et al, ; Narayan et al, ; Page et al, ; Stout et al, ; Tain et al, ; Teleman, Hietakangas, Sayadian, & Cohen, ). These include carbohydrate metabolism (Afschar et al, ), lipid and fatty acid metabolism (Dobson et al, ; Hahn et al, ; Murphy et al, ; Page et al, ), energy metabolism (Afschar et al, ), and protein and methionine (Met) metabolism (Narayan et al, ; Stout et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining the transcriptomic and proteomic changes that occur during aging, or in response to interventions that ameliorate its effects, have revealed several conserved prolongevity processes, including many metabolic changes (Afschar et al, ; Dobson et al, ; Hahn et al, ; Murphy et al, ; Narayan et al, ; Page et al, ; Stout et al, ; Tain et al, ; Teleman, Hietakangas, Sayadian, & Cohen, ). These include carbohydrate metabolism (Afschar et al, ), lipid and fatty acid metabolism (Dobson et al, ; Hahn et al, ; Murphy et al, ; Page et al, ), energy metabolism (Afschar et al, ), and protein and methionine (Met) metabolism (Narayan et al, ; Stout et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As an important mediator of insulin binding to its receptors and exerting biological effects, IRS1 plays an important role in the control of blood glucose homeostasis . A recent study suggests that the cause of insulin deficiency in obese patients may be due to a weakened IRS1 signal .…”
Section: Discussionmentioning
confidence: 99%
“…As an important mediator of insulin binding to its receptors and exerting biological effects, IRS1 plays an important role in the control of blood glucose homeostasis. 19 A recent study suggests that the cause of insulin deficiency in obese patients may be due to a weakened IRS1 signal. 20 A study of African-Americans found that IRS1 mutations and endocrine disorders caused by obesity synergistically reduce insulin sensitivity, suggesting that IRS1 variability and obesity together become an important predictor of insulin resistance.…”
Section: Gene Name Patient Num Patientmentioning
confidence: 99%
“…Interventions to disrupt the GH/IGF-1 (somatotropic) axis have been shown to have pro-longevity effects in mice. For example, mice with deletion of insulin receptor substrate 1 (IRS1) are long-lived with delay age-related processes [49]. Knockout of the mouse growth hormone receptor/binding protein (GHR/BP) gene also results in an extended lifespan [44,50,51].…”
Section: Signaling Network Of Foxo In Dr: Insulin/igf-1 Signaling Pamentioning
confidence: 99%